2021
DOI: 10.1177/07311214211012025
|View full text |Cite
|
Sign up to set email alerts
|

Worksites as Sacrifice Zones: Structural Precarity and COVID-19 in U.S. Meatpacking

Abstract: As meatpacking facilities became COVID-19 hotspots, the pandemic renewed the importance of longstanding claims from environmental justice and agrifood scholars. The former asserts the perceived dispensability of marginalized populations sustains environmental injustices, whereas the latter stresses that decades of industrial consolidation created structural instability in the food supply chain. This article asks how industry and government leverage existing socio-ecological inequalities to ensure the continuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…A study of Canadian workers found that among low-income workers, immigrants and minorities faced a greater risk of COVID exposure at work, thus adding a health-related dimension to our understanding of racialized job stratification (St-Denis 2020, 402). A similar effect could be found in the U.S. meatpacking industry, where government intervention forced a largely immigrant workforce to continue working in unsafe "sacrifice zones" in the name of national interest (Carrillo and Ipsen 2021). This article joins this literature in exploring how the process of welfare and regulatory state decline interacts with workers' status as immigrant in producing a disparate experience of the pandemic.…”
Section: Introductionmentioning
confidence: 63%
“…A study of Canadian workers found that among low-income workers, immigrants and minorities faced a greater risk of COVID exposure at work, thus adding a health-related dimension to our understanding of racialized job stratification (St-Denis 2020, 402). A similar effect could be found in the U.S. meatpacking industry, where government intervention forced a largely immigrant workforce to continue working in unsafe "sacrifice zones" in the name of national interest (Carrillo and Ipsen 2021). This article joins this literature in exploring how the process of welfare and regulatory state decline interacts with workers' status as immigrant in producing a disparate experience of the pandemic.…”
Section: Introductionmentioning
confidence: 63%
“…Critics, however, posit that this prevailing market power approach leaves out those hurt most directly by consolidation: workers, farmers, and rural communities (Hendrickson et al 2020;Garcés 2020). Further, they suggest that such commodity or product specific approaches to market power overlook intersectoral dependencies that lead to supply chain failures alongside human and animal suffering, exemplified by the fallout of COVID-19 hotspots at industrial meat processing facilities (Hendrickson 2020;Carrillo and Ipsen 2021). Reduced transaction costs are a matter of legal rights afforded to the largest corporate conglomerates, leaving them the beneficiaries of the efficiency argument by design (Paul 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(Cruz forthcoming,4) The government also failed the meatpacking workers. As Cruz and others note, the federal agency responsible for oversight of the industry, the Occupational Safety and Health Administration (OSHA), was vastly understaffed, manifesting "decades of underfunding, political puppeteering, and catering to employer-friendly policies" (ibid., 5; see also Marks 2022;Carrillo and Ipsen 2021). But it also did little to intervene, even after receiving thousands of COVID-related workplace safety complaints.…”
Section: Expropriation Of the Underpaid: Essential Migrant Labormentioning
confidence: 99%